Influence of 45S5 Bioactive Glass in A Standard Calcium Phosphate Collagen Bone Graft Substitute on the Posterolateral Fusion of Rabbit Spine - Pugely, Andrew J. (Iowa Orthop J, 2017)
INTRODUCTION: Spinal fusion surgery is an effective but costly treatment for select spinal pathology. Historically iliac crest bone graft (ICBG) has remained the gold standard for achieving successful arthrodesis. Given well-established morbidity autograft harvest, multiple bone graft replacements, void fillers, and extenders have been developed. The objective of this study was to evaluate the in vivo efficacy and safety of two mineralized collagen bone void filler materials similar in composition. Both bone void fillers were composed of hydroxyapatite (HA), tricalcium phosphate (TCP) and bovine collagen. The first test article (Bi-Ostetic bioactive glass foam or “45S5”) also contained 45S5 bioactive glass particles while the second test article (Formagraft or “FG”) did not. 45S5 and FG were combined with bone marrow aspirate and iliac crest autograft and compared to ICBG in an established posterolateral spine fusion rabbit model. MATERIALS AND METHODS: Sixty-nine mature New Zealand White rabbits were divided into 3 test cohorts: ICBG, 45S5, and FG. A Posterolateral fusion model previous validated was utilized to assess fusion efficacy. The test groups were evaluated for spine fusion rate, new bone formation, graft resorption and inflammatory response using radiographic, μCT, biomechanical and histological endpoints at 4, 8 and 12 weeks following implantation. RESULTS: There were 4 clinical complications unrelated to the graft materials and were evenly split between groups (ICBG graft harvest complications; hind limb mobility, chronic pain) and were euthanized. These omissions did not affect the overall outcome of the study. Radiographic scoring of the fusion sites indicated a normal healing response in all test groups, with no adverse reactions and similar progressions of new bone formation observed over time. All groups demonstrated significantly less range of motion in both flexion/extension and lateral bending compared to normal not-fused controls, which supports fusion results observed in the other endpoints. Fusion occurred earlier in the 45S5 group: ICBG 0%, FG 0%, and 45S5 20% at 4 weeks; ICBG 43%, FG 38%, and 45S5 50% at 8 weeks; and ICBG 50%, FG 56%, and 45S5 56% at 12 weeks. Histopathology analysis of the fusion masses, from each test article and time point, indicated an expected normal response for resorbable calcium phosphate (HA/TCP) and collagen graft material. Mild inflammation with macrophage and multinucleated giant cell response to the graft material was evident in all test groups. DISCUSSION: This study has confirmed the biocompatibility, safety, efficacy and bone healing characteristics of the HA-TCP collagen (with or without 45S5 bioactive glass) composites. The results show that the 3 test groups had equivalent long-term fusion performance and outcome at 12 weeks. However, the presence of 45S5 bioactive glass seemed to accelerate the fusion process as evidenced by the higher fusion rates at 4 and 8 weeks for the HA-TCP-collagen composite containing bioactive glass particles. The results also demonstrate that the HA-TCP-45S5 bioactive glass-collagen composite used as an extender closely mirrors the healing characteristics (i.e. amount and quality of bone) of the 100% autograft group.